Perbandingan Daya Ledak Otot Tungkai Antara Rasio Panjang Tungkai Atas dan Bawah > 1 dan < 1 - Panditama, Yukta; Subrata, Tanjung; Udiyani, Desak Putu Citra (Universitas Ciputra Surabaya, 2024)
Muscle explosive power is a person's ability to perform explosive activities suddenly and quickly by exerting all the strength in a short time. The explosive power of the leg muscles is influenced by the length of the leg. The purpose of this study was to find out the comparison of leg muscle explosive power between ratio of upper and lower leg length more than 1 and less than 1. The method of this study was using an analytic observational design with a cross-sectional approach. This study was carried out on 50 male Warmadewa University students who participate in basketball extracurriculars. The study data was analyzed by SPSS program. The results were showed as follow: the average of leg muscle explosive power in all subject and in subjects with a leg length ratio more than 1 and less than 1 were 21,62 ± 3,43 cm; 22,02 ± 3,51 cm; and 19,14 ± 1,34 cm respectively. The conclusion could be drawn that the comparison was significant. This study suggests that the selection of basketball players/athletes should be choosen palyers/athletes with an upper and lower leg length ratio of more than 1.